If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(m + 4) = 4 Reorder the terms: -3(4 + m) = 4 (4 * -3 + m * -3) = 4 (-12 + -3m) = 4 Solving -12 + -3m = 4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -3m = 4 + 12 Combine like terms: -12 + 12 = 0 0 + -3m = 4 + 12 -3m = 4 + 12 Combine like terms: 4 + 12 = 16 -3m = 16 Divide each side by '-3'. m = -5.333333333 Simplifying m = -5.333333333
| y=(7x+9)(x-1) | | 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x | | 7x-6=3(x^6) | | (12x+10)-(-4x-6x+10)= | | 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) | | Y=2500-2x | | 10x+4x+4+9=4x+3+9x | | x^2+4x=47 | | 3.91x+16=15.2881+4x | | 3cosx=8-4secx | | v^2=18v | | -5(4b+4)+(21b-7)=0 | | R^2-4r-6=0 | | (x^2-10x)+(y^2-6y)=-33 | | y(-2)=-6.8(-2)+5 | | 3x+4(2x-12)=73 | | 5y+18y-(-2y)+(-10y)= | | 0.12=0.5y | | 0.12=0.5 | | 5m-7=12 |